Influence of Ionophore Supplementation on Growth Performance, Dietary Energetics and Carcass Characteristics in Finishing Cattle during Period of Heat Stress - Barreras, A. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
Forty-eight crossbred heifers (378.1±18 kg) were used in a 56-d feeding trial (four pens per treatment in a randomised complete block design) to evaluate the influence of ionophore supplementation on growth performance, dietary energetics and carcass characteristics in finishing cattle during a period of heat stress. Heifers were fed a diet based on steam-flaked corn (2.22 Mcal NE(m)/kg) with and without an ionophore. Treatments were: i) control, no ionophore; ii) 30 mg/kg monensin sodium (RUM30); iii) 20 mg/kg lasalocid sodium (BOV20), and iv) 30 mg/kg lasalocid sodium (BOV30). Both dry matter intake (DMI) and climatic variables were measured daily and the temperature humidity index (THI) was estimated. The maximum THI during the study averaged 93, while the minimum was 70 (THI average = 79.2±2.3). Compared to controls, monensin supplementation did not influence average daily gain, the estimated NE value of the diet, or observed-to-expected DMI, but tended (p = 0.07) to increase (4.8%) gain to feed. Compared to controls, the group fed BOV30 increased (p≤0.03) daily gain (11.8%), gain to feed (8.3%), net energy of the diet (5%), and observed-to-expected DMI (5.2%). Daily weight gain was greater (7.6%, p = 0.05) for heifers fed BOV30 than for heifers fed MON30. Otherwise, differences between the two treatments in DMI, gain to feed, and dietary NE were not statistically significant (p>0.11). Plotting weekly intakes versus THI, observed intake of controls was greater (p<0.05) at THI values ≤77 than ionophore groups. When THI values were greater than 79, DMI of control and MON30 were not different (p = 0.42), although less than that of groups fed lasalocid (p = 0.04). Variation in energy intake was lower (p>0.05) in the ionophores group (CV = 1.7%) than in the control group (CV = 4.5%). Inclusion of ionophores in the diet resulted in relatively minor changes in carcass characteristics. It is concluded that ionophore supplementation did not exacerbate the decline of DM intake in heat-stressed cattle fed a high-energy finishing diet; on the contrary, it stabilised feed intake and favoured feed efficiency. Ionophore supplementation reduced estimated maintenance coefficients around 10% in finishing cattle during a period of heat stress. This effect was greatest for heifers supplemented with 30 mg lasalocid/kg of diet.